SISTEM INFORMASI REKRUTMEN KARYAWAN BERBASIS WEB MENGGUNAKAN ALGORITMA SAW (SIMPLE ADDITIVE WEIGHTING) - Nur Alamsyah (FKOM UNIKU, 2020)
This research aims to develop a system of employee recruitment. Generally, the stages of employee recruitment systems still use manual system methods, such as receiving prospective employee application documents and conducting psychological tests directly by giving questions in paper form. This way is considered less efficient because it takes long time. One way to overcome the problems described above is by having a web-based recruitment information system that is able to provide information about job vacancies for prospective employees as well as the stages of the employee recruitment process such as document selection, online psychological testing. By using appropriate technology, it is expected to provide improvement and it can develop a system that is originally a manual into an information system that is faster, easier and more efficient in recruiting employees by using a Decision Support System to support the decision-making stage of identifying problems, selecting relevant data, determining the approach used in the decision making process which uses the Simple Additive Weigthing (SAW) method. The methodology used to design and build a decision support system is the Ration Unified Process (RUP). Unified Modeling Language (UML) is used for design Keywords : CRM, Hotelmu, Object Oriented, Prototype